AUTOIMMUNITY AS A COMPLICATION OF VIRAL INFECTIONS: SIGNIFICANCE FOR THE DEVELOPMENT OF AUTOIMMUNE AND ONCOLOGICAL DISEASES - Monika Czekalska; Patrycja Jędrzejewska-Rzezak; Kinga Knutelska; Natalia Kulicka; Aleksandra Winsyk; Paulina Gajniak; Maciej Karwat; Tytus Tyralik; Klaudia Bilińska; Joanna Węgrzecka (International Journal of Innovative Technologies in Social Science, 2025)
Viral infections play a key role in the initiation of autoimmune processes and the development of virus-associated cancers. This review presents current knowledge on the mechanisms leading to autoimmunity following viral infections, such as molecular mimicry, epitope spreading, activation of the bystander phenomenon, and deregulation of regulatory T cells. Examples of infection-related autoimmune diseases (SLE, multiple sclerosis, Guillain-Barré syndrome, autoimmune thyroiditis) and the impact of COVID-19 as a trigger for new disease entities are also discussed. Particular attention is paid to the role of oncogenic viruses (HPV, HBV, HCV, EBV, HTLV-1) and chronic immunosuppression in the initiation of malignant transformation, as well as the mechanisms of tumor microenvironment formation. The intersection of autoimmunity and immuno-oncology is presented, including the relationship between the occurrence of adverse effects of immunotherapy and treatment efficacy. The importance of biomarkers (ANA, ENA antibodies, cytokine profile) in diagnosis and the challenges in differentiating autoimmunity from early-stage cancers are also discussed. The final section presents therapeutic and preventive strategies, including the role of vaccination, patient monitoring, and immunomodulation. The need for multicenter prospective studies and the development of personalized treatment methods is emphasized. This topic has significant clinical and health implications, particularly in the post-pandemic era, where the incidence of autoimmune disorders and cancers associated with viral infections is increasing.